Juckende Papeln submammär - Hamsch, Corinna; Hadaschik, Eva (Der Hautarzt, 2012)
Focal, mostly suprabasal acantholyis with development of dyskeratotic keratinocytes are typical histological features of Grover’s disease. The histological distinction between other forms of acantholytic dermatoses is often difficult. A combined assessment of the histological findings and the clinical symptoms often allows a clear diagnosis. The disease is self-limiting but treatment is necessary in some cases due to the sometimes excessive pruritis.